Improvement in the grinding process using the MQL technique with cooled wheel cleaning jet - Javaroni, Rafael Liberatti [UNESP]; Lopes, Jose Claudio [UNESP]; Diniz, Anselmo Eduardo; Garcia, Mateus Vinicius [UNESP]; Fonteque Ribeiro, Fernando Sabino; Tavares, Andre Bueno [UNESP]; Talon, Anthony Gaspar [UNESP]; Angelo Sanchez, Luiz Eduardo de [UNESP]; Mello, Hamilton Jose de [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Elsevier B.V., 2020)
In grinding, the viability of the minimum quantity lubrication (MQL) technique is still limited, due to the frequent occurrence of overheating and wheel clogging. Thus, MQL improvement is essential to allow its extensive application in grinding processes. This work evaluates a cooled wheel cleaning jet (CWCJ) under different temperatures, applied simultaneously to the MQL in grinding of AISI 4340 hardened steel. Tests with the conventional, MQL, and MQL + WCJ methods were also performed for comparison. The assessed output parameters were workpiece surface roughness, microhardness and roundness deviation, diametrical wheel wear, and grinding power. The machined surfaces and the chips were evaluated through scanning electron microscopy. The application of the CWCJ enhanced the performance of the MQL technique.
Keywords: Grinding; Minimum quantity lubrication; Cooled wheel cleaning jet; Surface integrity